2012
DOI: 10.1017/s0952675712000024
|View full text |Cite
|
Sign up to set email alerts
|

Lenition, fortition and the status of plosive affrication: the case of spontaneous RP English/t/

Abstract: This paper reports on a phonetic and phonological study of /t/-affrication in spontaneous British English Received Pronunciation. The study is motivated by the uncertainty surrounding plosive affrication in the literature on lenition and fortition. We suggest that a decision as to the status of a given pattern involving affrication in terms of lenition or fortition should be based on thorough phonetic and phonological analysis. We present a phonetic and phonological account of /t/-affrication, which takes into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…BE is characterised by pre-pausal devoicing, since only voiceless stops, fricatives and affricates occur word-finally before a pause, resembling the Bena L1 pattern. Unlike in Bena but like in more standard varieties of NE, as well as British RP English (Buizza & Plug 2012), pre-pausal stops normally have audible release which may be strong enough to qualify as aspiration (figure 1a), and pre-pausally, occasionally even as a slight affrication (figure 1b). At times, pre-pausal oral stops are glottalised as in Bena but unlike in more standard varieties of NE, viz.…”
Section: Bena English (L2) Consonantsmentioning
confidence: 99%
“…BE is characterised by pre-pausal devoicing, since only voiceless stops, fricatives and affricates occur word-finally before a pause, resembling the Bena L1 pattern. Unlike in Bena but like in more standard varieties of NE, as well as British RP English (Buizza & Plug 2012), pre-pausal stops normally have audible release which may be strong enough to qualify as aspiration (figure 1a), and pre-pausally, occasionally even as a slight affrication (figure 1b). At times, pre-pausal oral stops are glottalised as in Bena but unlike in more standard varieties of NE, viz.…”
Section: Bena English (L2) Consonantsmentioning
confidence: 99%
“…Word-medial intervocalic /t/ is also subject to complex variation in NZE and other varieties, as it can undergo a multitude of phonological processes that include frication, voicing, flapping, and glottalization; Hay and Foulkes (2016) report at least ten variants. Unsurprisingly, the acoustic cues associated with variation in medial /t/ (and English /t/ in other contexts; Temple, 2014) are likewise complex; frication is associated with a greater center of gravity, spectral dispersion, and kurtosis (Jones & Llamas, 2008;Jones & McDougall, 2009), and shorter duration (Buizza & Plug, 2012); voicing is associated with the presence of periodicity (Riehl, 2003); flapping with weakened F2 and F3 (Warner & Tucker, 2011); and glottalization with decreased formant transitions (Docherty & Foulkes, 1999) and increased spectral tilt (Seyfarth & Garellek, 2015). Within sociolinguistics, to simplify this complex variation and facilitate statistical modeling, medial /t/ variants are sometimes collapsed into binary categories.…”
Section: Medial /T/mentioning
confidence: 99%
“…There are some limited comments on the realisations of the stop in nasal-stop clusters in British English. Glottalisation (Docherty 1992) or affrication (Buizza & Plug 2012) of the stop may occur in nasal-stop clusters. While lenition of final stops is a well-known feature of Liverpool English (Wells 1982;Hughes & Trudgill 1996;Honeybone 2001), recent studies have shown that final stops preceded by nasals are unlikely to lenite (Honeybone 2001;Watson 2006).…”
Section: Nasal-obstruent Clustersmentioning
confidence: 99%
“…In particular, there is a wide range of research dealing with variation in the realisation of nasal–stop clusters in American English (see, for example, Malécot 1960; Selkirk 1972; Ali et al 1979; Fujimura 1981; Cohn 1993; Guy & Boberg 1997; Zue & Laferriere 1997; Warner 2002). However, there has been comparatively little research on nasal–obstruent clusters in British English varieties (Docherty 1992; Buizza & Plug 2012).…”
Section: Introductionmentioning
confidence: 99%